2005
DOI: 10.1007/s10611-006-9006-8
|View full text |Cite
|
Sign up to set email alerts
|

Sociolegal change in consumer fraud: From victim-offender interactions to global networks

Abstract: Advances in technology have transformed fraud against consumers from face-toface, victim-offender interactions to a crime that now transcends international boundaries. Although consumer protection issues have been of interest to investigative journalists and literary scholars for centuries, the topic has only recently been subject to serious criminological inquiry. Employing the American consumer protection movement as an historical framework, we examine the evolution of consumer fraud. Our review documents th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…These modes of commerce are not deviant and represent regular, day-to-day lifestyle choices made by a large number of adult consumers. Although many transactions between vendors and consumers still involve face-to-face, in-person communication in settings monitored by capable guardians (e.g., grocery shopping at the local market), advances in technology have increased opportunities for social exchange via a variety of additional mechanisms (Holtfreter, Van Slyke, and Blomberg, 2005;Vohs and Faber, 2007). Approximately 75 percent of American households have access to the Internet (Nielson Ratings, 2004), and an estimated 97.6 percent of American households have telephones (U.S. Census Bureau, 2004).…”
Section: Victimization Risk and Routine Activity Theorymentioning
confidence: 99%
“…These modes of commerce are not deviant and represent regular, day-to-day lifestyle choices made by a large number of adult consumers. Although many transactions between vendors and consumers still involve face-to-face, in-person communication in settings monitored by capable guardians (e.g., grocery shopping at the local market), advances in technology have increased opportunities for social exchange via a variety of additional mechanisms (Holtfreter, Van Slyke, and Blomberg, 2005;Vohs and Faber, 2007). Approximately 75 percent of American households have access to the Internet (Nielson Ratings, 2004), and an estimated 97.6 percent of American households have telephones (U.S. Census Bureau, 2004).…”
Section: Victimization Risk and Routine Activity Theorymentioning
confidence: 99%
“…Although there has been a considerable amount of research on the public's attitudes toward violent crime, little is known about current American perceptions of white-collar crime. Recent, well-publicized scandals in major corporations, such as Enron and WorldCom, have raised public awareness of the economic, societal, and personal harm resulting from "crime in the suites" (Holtfreter, Van Slyke, & Blomberg, 2005;Krantz, 2003;O'Donnell & Willing, 2003). A recent public opinion poll found that over 75 percent of those surveyed believed ex-WorldCom CEO Bernard Ebbers' twenty-five year sentence for his role in this extensive corporate fraud was fair or not harsh enough (Wall Street Journal Opinion Poll, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To address these empirical gaps, we explore how online fraud is perpetrated and perpetuated (Holtfreter et al 2005), focusing on the multiple communications between online scammers and victims. To frame these communications, we adopt the criminal event perspective (Lukenbill 1977;Meier, Kennedy, and Sacco 2001) and draw on "Interpersonal Deception Theory" (Buller and Burgoon 1996) to form hypotheses regarding the role of criminal opportunities (Briar and Pilavin 1965) in conditioning the effect of initial deception displays of urgency on subsequent deceptive cues.…”
Section: Online Fraudmentioning
confidence: 99%